Biosecurity-Based Good Aquaculture Practices for Sustainable Aquaculture Environmental Management: A Literature Review - Zamzami, Zamzami (Jurnal KESANS : Kesehatan dan Sains, 2026)
Introduction: The rapid development of aquaculture contributes to meeting global fish protein demand; however, it also poses environmental challenges such as declining water quality, increased aquaculture waste, and heightened risks of disease transmission. Objective: This article aims to examine the role of biosecurity-based Good Aquaculture Practices (GAP) in supporting sustainable aquaculture environmental management. Method: This study employed a literature review method with a content analysis approach, drawing on relevant national and international scientific articles. Results and Discussion: The findings indicate that the implementation of biosecurity-based GAP contributes to improved water quality and waste management, enhanced sanitation and fish health management, and reduced use of antibiotics and chemicals that may contaminate the environment, with successful implementation influenced by managerial support and policy frameworks. Conclusion: Biosecurity-based Good Aquaculture Practices represent an important approach to aquaculture environmental management, as they support the sustainability of aquaculture activities while minimizing negative impacts on aquatic environments